2020
DOI: 10.1177/2151459320972681
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Mortality in COVID-19 Positive Patients With Hip Fractures: A Case-Series and Literature Review

Abstract: Introduction: The novel coronavirus has spread rapidly around the world with particularly high mortality in the elderly. Care and nursing homes have become the sites of greatest concentration of cases. We intended to review 30-day mortality of COVID-19 patients with hip fractures. This is relevant given the disease impact in this age group. Methods: Medline and Embase databases were searched for relevant studies linked to mortality and morbidity in COVID-19 patients who have undergone non-elective hip surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [ 3 , 12 , 18 , 28 , 32 36 ]. In this study, none of the confirmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [ 3 , 12 , 18 , 28 , 32 36 ]. In this study, none of the confirmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increased mortality rate among patients with hip fractures who were diagnosed with COVID-19 [3,11,16,24,[27][28][29][30][31]. In this study none of the con rmed or suspected COVID-19 patients died in-hospital so the COVID-19 diagnosis may not be driving this increased risk for mortality.…”
Section: Discussionmentioning
confidence: 59%
“…The youngest of our patients was 70 years, and most of them presented comorbidities, frequently hypertension and diabetes. Moreover, COVID-19-positive patients with hip fractures, who may be similar to those with periprosthetic fractures except for the fact that the latter usually undergo a more invasive procedure, have shown a higher 30-day mortality rate compared with non-COVID-19 infected cases [ 7 ], and, more broadly, a meta-analysis revealed a very high global rate of post-operative mortality among COVID-19 patients of 20% and a post-operative intensive care unit (ICU) admission rate of 15% [ 34 ]. The patient’s immune function has been reported as a major determinant of the disease’s severity [ 35 ], and surgery may cause both an immediate impairment of immune function and an early systemic inflammatory response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that epidemiological characteristics may affect the prognosis of COVID-19 [ 5 ]. Moreover, literature data suggest that COVID-19 affects older patients and those with comorbidities most severely [ 6 , 7 ]. Patients with periprosthetic fractures (PPFs) are often old and with comorbidities.…”
Section: Introductionmentioning
confidence: 99%